Antibacterial activity of α-terpineol may induce morphostructural alterations in Escherichia coli - Li,Li (2014)
The antibacterial effect of α-terpineol from Cinnamomum longepaniculatum (Gamble) N. Chao leaf essential oils were studied with special reference to the mechanism of inhibiting the standard strain of Escherichia coli (CMCC (B) 44102) growth at ultrastructural level. Minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) and time-kill curves of α-terpineol were determined; Escherichia coli was treated with α-terpineol and observed under a transmission electron microscope. The MIC and MBC values of α-terpineol were all 0.78 µL/mL, and time-kill curves showed the concentration-dependent. Under the transmission electron microscopy (TEM), Escherichia coli exposed to MIC levels of α-terpineol exhibited decreased cell size and irregular cell shape, cell wall and cell membrane were ruptured, nucleus cytoplasm was reduced and nuclear area gathered aside. Results suggest that α-terpineol has excellent antibacterial activity and could induce morphological changes of Escherichia coli.